RFID en el servicio bibliotecario de la UTM - Pinargote-Ortega, Jenmer Maricela; Cruz-Felipe, Marely del Rosario; Demera Ureta, Gabriel Primitivo; Escobar-Moreira, Rubén Darío; Medranda-Cobeña, Gema Isabel (Revista Científica, 2019)
The central library of the Technical University of Manabí (UTM), offers the service of electronic equipment loans (laptops and tablets), in which theft has been presented. In the present article the integration of identification technologies through a web application is exposed. To do this, the requirements were raised, systems analysis and identification technologies were analyzed. Based on the study of art, the development methodology, programming languages, tools and technologies applied in the solution were described, the system architecture was designed with visual / audible alarm, the integrating system was developed and implemented and finally functional tests were carried out. As a result, it was evidenced that using bar code and RFID technology in the library service, there is better control of the entry and exit of electronic equipment, preventing any attempt at theft, and the university and general community receive a quality and speedy service.